First record of the genus Pseudopothea from South America, with description of a new species from Brazil (Hemiptera: Heteroptera: Reduviidae: Ectrichodiinae) - Gil-Santana, Hélcio R. (Zootaxa, 2015)
Pseudopothea paulai sp. nov. from Brazil is described based on male and female specimens. Sexual dimorphism of this species is documented. A revised diagnosis and the first record of Pseudopothea Wygodzinsky, 1951 from South America are furnished.